Acute Respiratory Distress Syndrome in the Trauma Intensive Care Unit: the Other View - Cedeño, Arturo; Rodríguez, Pablo; Rodríguez-Cintrón, William (Puerto Rico Health Sciences Journal, 2012)
see manuscript